Hubungan Antara Kepatuhan Pembatasan Asupan Cairan Dengan Lama Menjalani Hemodialisis Pada Pasien Gagal Ginjal Kronis - hasbyalloh, mochamad salman; Agustina, Mawar Suci; Rianto, Budi (Jurnal Kesehatan Bhakti Husada, 2024)
Chronic renal failure is a global health issue that also affects Indonesia. Chronic renal failure is a type of kidney failure in which there has been a steady loss of kidney function and no recovery. Hemodialysis treatment is necessary for a prolonged period of time in order to sustain chronic renal disease. Analytical observational research using a cross-sectional time approach is the methodology. Through the use of a complete sample technique, the study's population consisted of 55 hemodialysis patients. A formula called Kolmogorof-Smirnov is used in data analysis. The study's findings demonstrated that 32 participants (58.2%) in the old category had been receiving hemodialysis for a longer period of time, 12 participants (21.8%) in the moderate category had adhered to fluid intake limitations, and in the new category there were 11 individuals (20.0%). The Kolmogorof-Smirnov statistical test yielded a significant value of p < 0.05 and a value of p = 0.026. At Cimacan Regional General Hospital, patients with chronic renal failure who adhere to fluid consumption limitations have a correlation with the length of time they have been receiving hemodialysis. It is anticipated that individuals with chronic renal failure, whether recently diagnosed or long-term hemodialysis patients, would continue to enhance compliance with fluid intake guidelines in order to avoid problems.